2015
DOI: 10.1111/trf.12974
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐K formation is not associated with the storage time of transfused red blood cells

Abstract: Within the range of storage times used in normal clinical practice in the Netherlands, no association could be found between RBC storage time and anti-K formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In the study with the highest proportion of these specificities almost 30% of the patients had a transfusion history suggesting that an antigen booster is necessary to reach detectable antibody levels to these antigens . Regarding Rh and K antibodies, we observed that in the majority of responding patients, 1 to 2 incompatible units (RBCs or PLTs) were sufficient to induce antibodies, confirming the relative high immunogenicity of these antigens (D. Evers, R.A. Middelburg, S. Zalpuri, et al, submitted for publication) …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the study with the highest proportion of these specificities almost 30% of the patients had a transfusion history suggesting that an antigen booster is necessary to reach detectable antibody levels to these antigens . Regarding Rh and K antibodies, we observed that in the majority of responding patients, 1 to 2 incompatible units (RBCs or PLTs) were sufficient to induce antibodies, confirming the relative high immunogenicity of these antigens (D. Evers, R.A. Middelburg, S. Zalpuri, et al, submitted for publication) …”
Section: Discussionsupporting
confidence: 60%
“…7 Regarding Rh and K antibodies, we observed that in the majority of responding patients, 1 to 2 incompatible units (RBCs or PLTs) were sufficient to induce antibodies, confirming the relative high immunogenicity of these antigens (D. Evers, R.A. Middelburg, S. Zalpuri, et al, submitted for publication). 29 Residual non-D-matched RBC in PLT products have been reported to be the offender of anti-D in mainly immunosuppressed hematooncology patients, with reports of 0% to 14%, [30][31][32] while non-D antibodies have been scarcely reported. [33][34][35] In this study seven non-D antibodies (five anti-E, one anti-e and anti-K) were formed by six EM patients after cognate antigen exposure through (nonmatched) PLT transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Use of K– units to prevent alloimmunization in young females would be an additional benefit of mass phenotyping programs. There has been interest in introducing further measures to prevent D alloimmunization, such as genotyping of D– donors to find D variants that may be missed on serologic typing . In countries such as Canada and the United States that have not implemented prophylactic measures to prevent K alloimmunization, a more effective way to further reduce HDFN may be to provide K‐matched units to female patients.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study did not find also any relationship between anti-K formation and storage time of transfused red blood cells. [36]. In humans with SCD, Fasano et al [25] found no correlation between immunization and the age of the RBCs used for transfusion.…”
Section: The Transfused Productsmentioning
confidence: 99%
“…A more recent study did not find also any relationship between anti‐K formation and storage time of transfused red blood cells. . In humans with SCD, Fasano et al .…”
Section: The Transfused Productsmentioning
confidence: 99%